Temperate Forest Floors: Ecosystem Hubs in Transition? - Friederike Lang; Jörg Prietzel; Frank Hagedorn; Klaus Kaiser; Stefanie Schulz; Mathias Mayer; Lars Vesterdal; Jürgen Bauhus; Maï Bergmann; Sebastian Bibinger; Martin I. Bidartondo; Jingxuan Olivia Chen; et al. (Global Change Biology, 2026)
The forest floor (FF) plays a key role in carbon, nutrient, and water cycling. It is the biologically most active compartment of forest soils, highly responsive to environmental conditions. Yet, its response to current changes in environmental conditions and forest management is understudied. Temperate forests are among the best studied ecosystems globally, providing the necessary ecological and biogeochemical background information to assess FF changes. Here, we focus on identifying existing knowledge and gaps in our understanding of the functioning of the FF. Interactions between FF biota and abiotic FF components show multifactorial dependencies with environmental conditions and drive FF turnover. Vice versa, the turnover of FF regulates carbon, nutrient, and water cycling. With slow litter decomposition and limited bioturbation, organic matter accumulates, nutrients cycle tightly within the FF, and water passes through this layer partly along preferential pathways. With rapid litter decomposition and intense bioturbation, FF accumulation is little, the mineral soil is the main nexus for plant nutrient uptake and organic matter transformation, and water infiltrates the mineral soil more homogeneously. The interconnectedness with the adjacent ecosystem compartments is a crucial feature of the FF, feeding back to its functioning and making it a central hub of forest processes. The FF morphology reflects these processes and therefore has untapped potential as an indicator of soil and ecosystem health. Under forest change, the FF might lose its functionality, with negative impacts on nutrient provision, water storage, and carbon sequestration. Consequences for forest growth could be strong and even detrimental. Hence, improved knowledge of FF characteristics and their linkages to mineral soils and aboveground ecosystem compartments is crucial for assessing forest resilience to progressing environmental changes.

Bundesweite Entwicklung der Grundwasserstände seit 1991: Langzeittrends, Variabilität und Auswirkungen der jüngsten Trockenphase - Maria Wetzel; Stefan Broda; Mariana Gomez; Markus Zaepke; Patrick Clos; Stefan Kunz; Tanja Liesch; Marc Ohmer; Bastian Habbel; Michel Wingering; Bernhard Pitschka; Antje Roucka; et al. (Grundwasser, 2026)
Zusammenfassung Die Studie untersucht die Entwicklung der Grundwasserstände in Deutschland anhand von 5844 Messstellen sowie deren Reaktionsdynamik gegenüber klimatologischen Antrieben im Referenzzeitraum 1991–2020. Zusätzlich wird die Entwicklung seit 2018 im Kontext der außergewöhnlichen Dürreperiode betrachtet, um die Reaktionsfähigkeit und Vulnerabilität der Grundwassersysteme gegenüber extremen klimatischen Bedingungen zu bewerten. Erstmals erfolgt diese Auswertung bundesweit einheitlich und in enger Zusammenarbeit mit den zuständigen Landesbehörden. An 43 % der untersuchten Messstellen werden signifikante Trends festgestellt, überwiegend in Form fallender Grundwasserstände mit einem Medianrückgang von 0,9 cm pro Jahr. Dies entspricht einem jährlichen Rückgang von 0,5 %, bezogen auf die Spannweite der jeweiligen Grundwasserganglinie. Diese Entwicklungen sind deutschlandweit erkennbar, jedoch regional unterschiedlich ausgeprägt und überwiegend klimatisch bedingt. Um Unterschiede in der Reaktionsdynamik systematisch zu erfassen, werden die Messstellen anhand ihrer Autokorrelationslängen in vier Dynamikklassen eingeteilt. Mit abnehmender Dynamik zeigt sich für den Referenzzeitraum eine Zunahme langfristiger Trends (von −0,3 % pro Jahr in Dynamikklasse 1 bis −1,16 % pro Jahr in Klasse 4) sowie eine höhere Persistenz klimatischer Effekte. Träge Systeme reagieren verzögert und sind damit nachhaltiger von Niedrigständen betroffen (Median: 9,8 Monate), während schnell reagierende Systeme kürzere Niedrigstandsphasen (Median: 2,2 Monate) aufweisen und sich rascher erholen. Besonders in der Entwicklung seit 2018 werden diese Unterschiede deutlich: Rund 60 % der trägen Messstellen weisen über fünf Jahre hinweg anhaltend niedrige Grundwasserstände auf, wobei etwa 20 % neue Niedrigstände erreichen und damit unterhalb der Minimalwerte der Referenzperiode liegen. Die Ergebnisse verdeutlichen den engen Zusammenhang zwischen klimatischer Variabilität und Grundwasserdynamik und bilden eine Grundlage für die fortlaufende Bewertung der Grundwasserstandsentwicklung in Deutschland.

Think pink 2.0 - Description of Roseobacter cerffii sp. nov., isolated from the chromerid alga Vitrella brassicaformis, and reclassification of Sulfitobacter sabulilitoris as Billmartinia sabulilitoris, gen. nov., comb. nov. - Jörn Petersen; Victoria Ringel; Orsola Päuker; Anja Frühling; Manfred Rohde; Michael Jarek; Cathrin Spröer; Boyke Bunk; Katharina Huber-Fischer; Silke Pradella; Heike M. Freese; Julia Koblitz; et al. (Systematic and Applied Microbiology, 2026)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

The dual H3/4R antagonist thioperamide does not fully mimic the effects of the ‘standard’ H4R antagonist JNJ 7777120 in experimental murine asthma - Detlef Neumann; Silke Beermann; Heike Burhenne; Silke Glage; Christina Hartwig; Roland Seifert (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Systematic analysis of histamine and N-methylhistamine concentrations in organs from two common laboratory mouse strains: C57Bl/6 and Balb/c - Anna Sophie Zimmermann; Heike Burhenne; Volkhard Kaever; Roland Seifert; Detlef Neumann (Inflammation Research, 2011)

Toxicity testing of heavy metals with theRhizobium-legume symbiosis: High sensitivity to cadmium and arsenic compounds - Heike Neumann; Anne Bode-Kirchhoff; Andrea Madeheim; Astrid Wetzel (Environmental Science and Pollution Research, 1998)